ANALISIS KAPASITAS DAYA DUKUNG PONDASI TIANG KERUCUK PADA BANGUNAN INSTALASI PENGOLAHAN LUMPUR TINJA KABUPATEN SIAK - Pribadi, Arqowi (Al-Ard: Jurnal Teknik Lingkungan, 2017)
IPLT of siak district is installation mud feces built in the district siak riau that launcher to serve around more or less 100.000 soul. The district siak generally soil structure consisting of land podsolik red yellow of rock and alluvial and tanah organosol and gley humus in the form of rawa-rawa or moist soil and building planned to be supplied bracing the ground as the kerucuk. This study aims to analyze the foundation of the kerucuk at every stage IPLT processing. Discharging from pillars foundation kerucuk is created one alternative for bracing of the ground at the land of pulpy/of land the wetness of ground a bog that are requisite and suited to increase carrying capacity of the land or reducing the incidence of of land subsidence related as a result of the construction of units liquid waste processing installations mud fecal matter kabupaten siak. Calculation a power capacity of support pillars foundation kerucuk performed on stage IPLT processing units siak district riau namely anaerobic ponds, the pool facultative, the pool maturasi, the pool solid separation chamber (SSC) and ponds in which a drying sludge bed (SDB). The analysis shows that the capacity of permission to one piece the foundation a wooden pole kerucuk with long in the depths of 12 ft 8 m from the surface of the native land of 4,648 tons. Keywords : mud feces, IPLT, kerucuk pilar foundation.